Disponibilidade de cálcio associada ao controle químico sobre o progresso da ferrugem asiática da soja - Silva, Angelica Marian da (2015)
The mineral nutrition is a tool that can be used in the management of diseases in soybean. Plants grown under adequate nutritional levels are more tolerant to attack by certain pathogens. Calcium is a structural component of the cell wall, its availability directly affects the mechanical strength of tissues and thus the reaction of the plant to plant pathogens. Other cropping practices than fungicides have to be searched to avoid excessive exposure of fungi to the same active ingredients, a fact favoring the emergence of resistant individuals. The study aimed to determine the effect of calcium availability on the severity of Asian soybean rust, plant growth and grain yield in two cultivars. The experiment was conducted in pots with sand in a greenhouse, from December 2, 2013 to April 15, 2014. The treatments consisted of a split-split-plot factorial (5x2x2) design, with five calcium concentrations in nutrient solution, two soybean cultivars and with and without chemical fungicide control. Seven evaluations of disease severity were made during the plant vegetative and reproductive stages and the area under the disease progress curve (AURPC) was determined. At the end of the experiment, shoot dry weight, grain production, total number of grains per plant, thousand grain weight and the leaf calcium content were determined. Results indicated that by increasing calcium availability shoot growth was enhanced and disease severity was reduced, grain production was increased in plants without chemical control, with interactions between cultivars. It was concluded that calcium nutrition can be used in crop management to reduce the severity of the Asian soybean rust.